Sugar alcohol-chelated calcium fertilizer enhances yield, quality and combustion performance in filler tobacco leaves - Sun, Jingguo; Zhai, Lindun; Tian, Huiwen; Chang, Yifei; Qiao, Baoming; Fan, Youlun; Chen, Tao; Xu, Rui; Zhang, Yunzheng; Rao, Yong; Chai, Liguang; Sun, Xuecheng (Frontiers in Agronomy, 2025)
IntroductionCigar filler tobacco, as the core component of cigars, determines combustion uniformity and smoking smoothness through its combustion performance.MethodsTo investigate the effects of calcium (Ca) fertilizers on the yield, quality, and combustion properties of filler tobacco leaves, the experiment used the cigar filler cultivar CX-14 (Chuxue No. 14) as the material, with sugar alcohol chelated Ca fertilizer as the Ca source. The field experiment included five Ca levels, with application rates (calculated as CaO) of 0 (CaO0), 40 (CaO40), 80 (CaO80), 120 (CaO120), and 160 kg/ha (CaO160). Thermogravimetric analysis was performed using a Q600 (TA-DSC) in an air atmosphere to study the weight loss and heat release behaviors of the tobacco leaves, and the Coats-Redfern integral method was applied to calculate the activation energy of the tobacco leaves.Results and DiscussionThe results showed that, compared to the control without Ca fertilizer, the yields of CaO40 and CaO80 treatments increased by 11.6% and 5.4%, respectively, and the proportion of premium tobacco leaves increased by 20.6% and 14.5%, respectively. The ash content of the tobacco leaves in the CaO40 and CaO80 treatments decreased by 31.9% and 27.5%, respectively. Ca fertilization primarily enhanced overall combustion performance by improving pyrolytic reactivity during Stage III (400-510°C) of the combustion process. During the III stage, compared to untreated tobacco, the activation energy of the tobacco leaves in the CaO40 treatment decreased by 5.6%, and the frequency factor increased by 73.2%; in the CaO80 treatment, the activation energy decreased by 3.1%, and the frequency factor increased by 23.5%. The combustion stability index and the comprehensive combustion characteristics index of the tobacco leaves treated with CaO80 were optimal, increasing by 34.5% and 33.9%, respectively, compared to the control. Based on the integrated effects on yield, economic value, and combustion performance, the optimal application rate of sugar alcohol-chelated Ca fertilizer (as CaO) is recommended to be between 40 and 80 kg/ha.